2022
DOI: 10.4236/ijg.2022.137030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Structural Framework and Depth Estimates Using High Resolution Airborne Magnetic Data over Some Parts of Middle Benue Trough, Nigeria

Abstract: High-resolution aeromagnetic data of parts of Middle Benue Trough, Nigeria (sheets 212, 213, 233 and 234) was interpreted by applying source Parameter Imaging (SPI) and Spectral Depth analysis with the aim of mapping out the magnetic lineaments and analysing magnetic signals coming from different sources. The results from the derivatives maps show major and minor lineaments trends in the NE-SW and NW-SE directions respectively. Results from SPI show the maximum sedimentary thickness of about −4546.7 m (−4.5467… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…While, the areas with low magnetic intensity values has widely spaced contours which signifies that the depth to the basement is relatively deeper. The study area has a major fault that is trending E-W (east-West) and other minor faults that equally trend in similar direction to the major fault according to Usman et al (2023) and Nasir et al (2022). Figure 5 shows the map of the analytical signal amplitude within the study area.…”
Section: Qualitative Interpretationmentioning
confidence: 91%
“…While, the areas with low magnetic intensity values has widely spaced contours which signifies that the depth to the basement is relatively deeper. The study area has a major fault that is trending E-W (east-West) and other minor faults that equally trend in similar direction to the major fault according to Usman et al (2023) and Nasir et al (2022). Figure 5 shows the map of the analytical signal amplitude within the study area.…”
Section: Qualitative Interpretationmentioning
confidence: 91%
“…The output can be interpreted as the one with very little variation and high variation when the values approach zero and large values respectively (Kovesi, 1991). Centre for exploration targeting was carried out to recognise linear structures contained within the aeromagnetic data through a repeated map by product forms that include standard deviation which determines variations in magnetic response (Abdulsalam et al, 2022), and the continues lines can be separated with phase symmetry. Afterwards, the resulting lineaments were enhanced by suppressing noise and background signals using amplitude thresholding (Figure 7).…”
Section: Centre For Exploration Targeting (Cet)mentioning
confidence: 99%
“…Qualitative analysis and interpretation of airborne magnetic and radiometric data have been very useful in identifying anomalous area(s) by delineating geological structures, lithological units, hydrothermal alteration zones and subsurface structures that might host economic and industrial minerals since magnetic minerals are structurally controlled (Abdulsalam et al,, 2022;Ologe et al,, 2018). O'leary et al, (1976), Ananaba & Ajakaiye (1987) concluded in their work that deformations are associated with most mineral deposits concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation